An ethical analysis of a home visit case study - Pibernat, Artur Dalfó (Nursing ethics, 2017)
This article will explore a clinical case study of a home visit carried out by the case manager nurse. In this case, we will discuss the dilemma of finding the balance between autonomy and beneficence from the perspective of principlist ethics, virtue ethics and the ‘ethics of care’. The main conflict in this case study deals with all proposals are unsuitable and it is not necessary for a nurse to pay him a home visit, whereas for the healthcare system it is considered necessary. We could conclude that, during the home visit, the case manager aspires to achieve excellence, and throughout his clinical relationship with Francesc, searches for a series of virtues, respecting certain fundamental principles. In this way, the case managers ensure that Jaume’s care is more humanised. The case has been anonymised and confidentiality maintained.